STRUKTUR PENYAJIAN TARI JAPPIN LAMBUT DI DESA SEKURA KECAMATAN TELUK KERAMAT KABUPATEN SAMBAS - Ariska, Haryati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract Tihis sense to describe and analyze the structceure of the presentation and implementation of ierning dance Jappin Lambut rural distcrits Sekura secred bay Sambas district. This research uses desceriptive method in the from qualitative and approach choreography. The sourece of the data in this study is Syahril, S.Pd and Solihin. Data coletcion techniques such as observation besed on data analisysis concluded that dence Jappin Lambut in the village Sekura disrici bay Sambas disrci structured presentation of the comportation of the presentation or appearance that has three parts most importation ti the presentation is part of the beginning middle and end. Poko encompasses elemense such as the presentation of dance, desigen on the desigen of the floor, the music accompaniment, makeup and dres and vanue. Therefore Jappin Lambut dance is a dsance that serves as an entertatinen and as a medium of propaganda aimed at spreding moral values associated whit the religion of Islam. Key wordes : struceture peresentation, dance Japin Lambut Sambas.